The relevance of non-invasive radiofrequency therapy for localized fat - Souza, D. S. T.; Vizioli, E. T.; Carvalho, T. T.; Berber, G. C. M. (Scientific Electronic Archives, 2018)
The present study reviewed the relevance of noninvasive radiofrequency treatment for localized fat through the Joule effect. This procedure promotes the conversion of radiation into heat in the tissues, providing some benefits, such as vasodilation, stimulation of the drainage system, reduction of free radicals and improvement of tissue oxygenation and nutrition. When administered in treatments for localized fat, a controlled temperature of 40 Â° C should be achieved through the infrared thermometer. Thus, radiofrequency promotes a friction between the adipocytes, generating the rupture. The cellular content that is extravagated is carried by the lymphatic system to the liver for metabolism. This study was carried out through a qualitative approach, through bibliographic findings with scientific knowledge aligned to the present problem. In conclusion, the literature indicates the use of radiofrequency in localized adiposity as an efficient aesthetic method.